Nature relatedness, connections to food and wellbeing in Australian adolescents. (December 2022) - Uhlmann, Kora; Ross, Helen; Buckley, Lisa; Lin, Brenda B.
Abstract: Adolescence is a critical developmental phase during which beneficial nature and food connections can be shaped. Currently nature relatedness research does not typically consider food as an integral component of nature. This exploratory study seeks to understand Australian adolescents' connections to nature and their food, and how these relate to their overall sense of wellbeing. A mixed methods approach combined an implicit association test with urban and rural adolescents, and a survey to measure nature relatedness, wellbeing, healthy food attitudes and behaviours. Most adolescents considered that food connected them with nature; however urban students were less likely than rural students to state specifically that food comes from nature. Meanwhile, family cohesion significantly predicts adolescent wellbeing and positive healthy eating attitudes. These findings suggest implications for effective strategies that foster sustainable healthy behaviours and opportunities for interaction with nature. Further, food and food production should be incorporated into future nature relatedness research, as well as nature relatedness considered in adolescent nutritional health research. Highlights: A new implicit association test was developed: food, nature and self connections. Adolescents felt more connected to food than to nature. Rural adolescents expressed deeper understanding of food-nature interconnectedness. Family cohesion is important for adolescent wellbeing and healthy eating attitudes. Food and food production should be incorporated into nature relatedness research.